Hubungan antara Dukungan Keluarga terhadap Konsep Diri pada Penderita Kusta di Desa Bangklean Kabupaten Blora - Fitra Ariyanta; Abi Muhlisin (Universitas Muhammadiyah Surakarta, 2017)
Family support for leprosy patients in the village of Blora Doplang Bangklean very low. In the beginning - the beginning of the patient suffering from leprosy families no supports at all for 2 to 4 months. Self-concept of the lepers in the village Bangklean is still low, they often isolate themselves from society as did the family. Every month on the 10th leper clinic to collect given medication and counseling, but that comes is only approximately 10 people from 28 people leprosy. This study aimed to investigate the relationship between self-concept support for families with leprosy patients in rural districts Bangklean Blora. This study is a quantitative correlation with a cross-sectional approach. The study population was a leper village Doplang Bangklean Blora as many as 28 people. Research instrument in the form of questionnaires. Analysis using the Chi-Square test. The study concluded that : (1) support the families in the village leper Bangklean Doplang Blora mostly low (54 %), (2) self-concept in patients with leprosy in the village Bangklean Doplang Blora mostly less (57 %), and (3) there is a family relationship with the concept of self- support in the leper village Doplang Bangklean Blora, where the better family support the concept of self leprosy patients getting better (p- value = 0.012)